Factors Affecting Optimal Titration Pressure of Continuous Positive Airway Pressure Device in Patients with Obstructive Sleep Apnea Syndrome - Kirgezen, Tolga; Bilici, Suat; Cakir, Mustafa; Ceyran, Ozlem; Chasan, Moustafa; Yigit, Ozgur (GALENOS YAYINCILIK, 2020)
Objective: To assess the effects of anatomical, clinical parameters, and pulmonary respiratory function on the therapeutic titration pressure of continuous positive airway pressure (CPAP) device in obstructive sleep apnea syndrome (OSAS). Methods: The study comprised 41 OSAS patients whose optimum CPAP titration pressures were measured. Each patient underwent an otorhinolaryngologic and thoracic examination, and data was recorded for height, weight, body mass index, neck-waist circumferences, Mallampati classification, tonsillar hypertrophy, hypopharyngeal collapse, soft palate-tongue base obstruction scores, peak nasal inspiratory flow and acoustic rhinometry measures, and CPAP device therapeutic pressures. Forced vital capacity, forced expiratory volume, FEV1/FVC ratio and peak expiratory flow values were noted. Results: Median CPAP optimal pressure cut-off value was determined as 9 mmH(2)O. Statistical analysis was made in two groups as CPAP titration optimal pressure <= 9 and >9 mmH(2)O. In the optimal pressure >9 group, neck and waist circumferences, hypopharyngeal collapse score, retropalatal and retrolingual lateral wall collapse scores were significantly higher (p<0.05). In multivariate and univariate model analysis, neck and waist circumferences, hypopharyngeal collapse score, retropalatal and retrolingual lateral wall collapse scores were observed to be significant in predicting high and low pressures in univariate model. Conclusion: For the prediction of optimal CPAP titration pressure in OSAS treatment, wide neck and waist circumferences, high hypopharyngeal collapse score and retropalatal and retrolingual lateral wall collapse grades may be determinative.
Keywords: Continuous positive airway pressure; apnea hypopnea index; obstructive sleep apnea syndrome; sleep disorder; CPAP titration